2019
DOI: 10.1002/lary.28170
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Does Not Increase the Risk of Sudden Sensorineural Hearing Loss: A National Cohort Study

Abstract: Objectives/Hypothesis Pregnancy‐induced systemic physiological changes appear to be associated with reversible hearing changes in pregnant/postpartum women. However, most studies are case reports due to the rare occurrence of sudden sensorineural hearing loss (SSNHL) during pregnancy. We aimed to evaluate the risk of SSNHL during the pregnancy and postpartum periods. Study Design A longitudinal case‐control study using a nationwide population cohort. Methods Using the Korean National Health Insurance Review an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In this study, KCD-6 codes related to delivery [ 19 21 ], pregnancy [ 19 , 22 , 23 ] and neonatal jaundice were selected to identify each event. Preterm delivery and multiple gestation were defined as at least one record of the related codes within 4 weeks before and after the delivery date.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, KCD-6 codes related to delivery [ 19 21 ], pregnancy [ 19 , 22 , 23 ] and neonatal jaundice were selected to identify each event. Preterm delivery and multiple gestation were defined as at least one record of the related codes within 4 weeks before and after the delivery date.…”
Section: Methodsmentioning
confidence: 99%
“…The decreased hearing thresholds never dropped past 25 dB pure tone average, which is not considered hearing loss by World Health Organization classification . A large database study did not find pregnant patients to be at greater risk of sudden sensorineural hearing loss . Nevertheless, sudden sensorineural hearing loss may occur in pregnant patients.…”
Section: Otolaryngologic Manifestations In the Pregnant Patientmentioning
confidence: 96%
“…6 A large database study did not find pregnant patients to be at greater risk of sudden sensorineural hearing loss. 7 Nevertheless, sudden sensorineural hearing loss may occur in pregnant patients. Although specific safety recommendations in pregnancy are not available for medications based on a lack of human and animal studies, use of intravenous dextran 40 and intratympanic steroids have been reported as safe in pregnant patients.…”
Section: Otolaryngologic Manifestations In the Pregnant Patientmentioning
confidence: 99%
“…A population-based study conducted in Taiwan covering data from 2000-2009 revealed an incidence of SSNHL of 2.71 per 100000 pregnancies, which is lower than that of the general female population[ 3 ]. Controversial results were reported by the South Korean study that compared the risks of SSNHL between pregnant females and non-pregnant populations[ 4 ]. Although vasospasm, hair cell lesions, and viral infections can explain the cause of the disease, the etiology for SSNHL in pregnant women seems to have different pathogenesis.…”
Section: Introductionmentioning
confidence: 99%